EFFECTS OF RESISTANCE TRAINING ON SPORTS PERFORMANCE COMPONENTS WITH RESPECT TO REACTION TIME AMONG PHYSICAL EDUCATION STUDENTS - Chavan, Prashant B. (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The purpose of the research was to effects the resistance training to improve sports performance -related Physical fitness components among different age groups physical education students with respect to Reaction Time Performance. The 40 newly admitted male physical education students consider as experimental group who was doing M. P. Ed. from School of educational science, S.R.T.M. University, Nanded were selected as subject for present study. Their age ranged between 21-30years and divided in 3 age Group (21-23, 24-26 and 27-30). Training was given to only experimental groups. The mean age of the experimental were 25.42 & 24.5, Height was 171.25 & 171.27cm and weight were 65.10 & 66.27kg. The Resistance Training was planned as 12 weeks 5 days a week and 90min. Study was conducted at S.R.T.M University Nanded. : For data analysis responses were expressed as Analysis of Covariance was performed for pre and post-test and Scheffe’s Post Hoc Test, that level of significant in the study should set up at 0.5 level. There was Significance effects of resistance training on performance-related physical fitness components with respect to Foot Reaction time in pre and post-test of physical education students. The training reveals that there was improvement of Foot Reaction Time in 24-26 age group. and Foot Reaction time in pre and post-test of 24-26 and 27-30 age group. The training reveals that there was improvement of Foot Reaction time in this age group physical education students.